Efektifitas Penyelesaian Sengketa Bisnis pada UMKM melalui Mediasi dan Arbitrase di Indonesia - Widya Hartati; Sandy Ari Wijaya (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, yet they are vulnerable to various conflicts that can hinder their continuity. Dispute resolution through legal channels (litigation) is often considered inefficient for MSMEs due to the lengthy process, high costs, and inflexibility. Therefore, alternative dispute resolution methods such as mediation and arbitration are considered preferable to litigation. This study aims to analyze the effectiveness of mediation and arbitration in resolving business conflicts among MSMEs in Indonesia, identify inhibiting factors in resolving business conflicts, and provide recommendations for strengthening the accessibility of these mechanisms for MSMEs. The research method used is empirical juridical, combining normative analysis of regulations governing mediation and arbitration with data collection using document studies related to MSMEs. The results indicate that mediation is generally more effective for MSMEs because it is less expensive, simpler, and can maintain business relationships between the parties. However, the success of mediation is also determined by the quality of the mediator and the willingness of both parties. On the other hand, arbitration provides legal certainty and a relatively quicker resolution process compared to litigation. However, the barriers are the relatively high cost and low legal understanding among MSMEs. A comparison of the two shows that the effectiveness of ADR depends heavily on the availability of information, support from service providers, and the MSME's ability to adapt to legal procedures.